ANALISIS SKALA ROSIER DALAM PENANGANAN STROKE AKUT DI RUANGAN IGD RSUD.PROF.DR.H. ALOEI SABOE KOTA GORONTALO - Damansyah , Haslinda; Umar, Arifin; Mokoagow, Cici R. (JURNAL KEPERAWATAN, 2023)
Background :Stroke is the leading cause of death in the world and continues to increase every year. The treatment of acute stroke in the emergency room in Indonesia varies greatly and has not specifically standardized the standards that must be done in the emergency room, so there will be many gaps that can harm patients. ROSIER is an instrument that can be used as an assessment in stroke patients to reduce the severity of stroke patients. Objective :The purpose of this study was to analyze the ROSIER scale in the management of acute stroke in the emergency room. Method :The method used in this study is quantitative research with an observational analytical approach, this study aims to analyze stroke management with the ROSIER Scale in the emergency room. Results :The results obtained are ROSIER scale analysis conducted on four nurses showing that two nurses are right to perform the rosier scale method in the treatment of acute stroke. While the other 2 nurses are not precise in carrying out the rosier scale method in the treatment of acute stroke. Conclusion :This shows that the Rosier scale method in treating stroke in the emergency room is still below 100%. It is hoped that health services, especially in the emergency room, can apply the Rosier assessment Keywords: Stroke ; ROSIER Scale; Stroke Management